Evaluación del uso de aceite esencial cymbopogon citratus stapf (Hierba luisa) en la conservación y almacenamiento de tres frutos de consumo masivo del mercado central del cantón Quevedo - Mora Silva, Grecia (2012)
In industrial projects are oriented to the rational use of natural resources for the production of products, with the practice of natural preservatives for the food industry, to ensure the conservation of fruits and avoid post-harvest losses especially targeted antimicrobial effects and prevent disease transmission through food. The application of chemical preservatives affecting consumers and the environment is one of the problems today, so they are running investigations which use organic products to ensure their effectiveness in reducing the degradation of fresh fruits and reduce development fungi, extending the life of them, moreover, to conservation will increase the storage time stressing improving marketing and increasing income. The aim of this study was to evaluate the use of essential oil (AE) Cymbopogon citratus Stapf "verbena" in the conservation and storage of three fruits of the central market consumer Quevedo Canton……